2022
DOI: 10.7554/elife.79396
|View full text |Cite
|
Sign up to set email alerts
|

A spatiotemporal reconstruction of the C. elegans pharyngeal cuticle reveals a structure rich in phase-separating proteins

Abstract: How the cuticles of the roughly 4.5 million species of ecdysozoan animals are constructed is not well understood. Here, we systematically mine gene expression datasets to uncover the spatiotemporal blueprint for how the chitin-based pharyngeal cuticle of the nematode Caenorhabditis elegans is built. We demonstrate that the blueprint correctly predicts expression patterns and functional relevance to cuticle development. We find that as larvae prepare to molt, catabolic enzymes are upregulated and the genes that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 94 publications
1
34
0
Order By: Relevance
“…For example EPIC-1 repeats 3-6 are perfect, as are EPIC-2 repeats 2 and 7. Other repetitive intrinsically disordered proteins have been identified in C. elegans aECMs such as the chitinous pharynx cuticle (Kamal et al, 2022) and suggest that aECMs may involve networks of intrinsically disordered proteins. Relative to imperfect repeats, perfect repeats have a higher tendency to be unstructured (Jorda et al, 2010) and are underrepresented in protein structure databases.…”
Section: Epicuticlins and Tandem Repeat Proteins In The Aecmmentioning
confidence: 99%
“…For example EPIC-1 repeats 3-6 are perfect, as are EPIC-2 repeats 2 and 7. Other repetitive intrinsically disordered proteins have been identified in C. elegans aECMs such as the chitinous pharynx cuticle (Kamal et al, 2022) and suggest that aECMs may involve networks of intrinsically disordered proteins. Relative to imperfect repeats, perfect repeats have a higher tendency to be unstructured (Jorda et al, 2010) and are underrepresented in protein structure databases.…”
Section: Epicuticlins and Tandem Repeat Proteins In The Aecmmentioning
confidence: 99%
“…Small molecule crystallization is restricted to the pharyngeal cuticle 5 , yet the collagens (which are highly abundant within the body cuticle) are also rich in -bonding capability 9 . Hence, there are likely additional properties of the pharynx cuticle beyond its amyloid-like nature that creates the unique niche that facilitates crystal formation.…”
Section: Insights Into Crystal Formation Within the C Elegans Pharynx...mentioning
confidence: 99%
“…We also constructed a spatiotemporal map for the development of the pharyngeal cuticle of C. elegans 9 . That study revealed the pharynx cuticle to be highly enriched with intrinsically disordered proteins (IDPs) and proteins with intrinsically disordered regions (IDRs) 9 . Many of these IDP and IDR-rich proteins have amyloidogenic features that include an enrichment in -bonding and hydrogen-bonding capabilities, and have protofilament formation propensity 9 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations